2009
DOI: 10.1038/ng.322
|View full text |Cite
|
Sign up to set email alerts
|

Differential chromatin marking of introns and expressed exons by H3K36me3

Abstract: Variation in patterns of methylations of histone tails reflects and modulates chromatin structure and function1-3. To provide a framework for the analysis of chromatin function in C. elegans, we generated a genome-wide map of histone H3 tail methylations. We find that C. elegans genes show similarities in distributions of histone modifications to those of other organisms, with H3K4me3 near transcription start sites, H3K36me3 in the body of genes, and H3K9me3 enriched on silent genes. Unexpectedly, we also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
576
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 606 publications
(628 citation statements)
references
References 36 publications
50
576
0
2
Order By: Relevance
“…We also confirmed that H3K36me3 and nucleosome were enriched at the exon boundaries (Fig. 3A) as previously reported (Kolasinska-Zwierz et al 2009;Schwartz and Ast 2010).…”
Section: H2bub1 Is Highly Enriched At the Exon-intron Boundaries Of Hsupporting
confidence: 92%
See 1 more Smart Citation
“…We also confirmed that H3K36me3 and nucleosome were enriched at the exon boundaries (Fig. 3A) as previously reported (Kolasinska-Zwierz et al 2009;Schwartz and Ast 2010).…”
Section: H2bub1 Is Highly Enriched At the Exon-intron Boundaries Of Hsupporting
confidence: 92%
“…Histone modifications are also involved in various cellular processes, including alternative splicing (Kolasinska-Zwierz et al 2009;Luco et al 2010). Several histone modifications can engage in crosstalk with other histone modifications, in either cis or trans.…”
mentioning
confidence: 99%
“…Remarkably, the pattern of these alterations was not irregular, raising a question of the underlying mechanism. Apart from alterations of cross-exon protein interactions and/or RNA secondary/tertiary structure, chromatin and histone modifications have been recently shown to influence splicing [Andersson et al, 2009;Gama-Carvalho et al, 1997;Kolasinska-Zwierz et al, 2009;Kornblihtt et al, 2009;Schor et al, 2009;Tilgner et al, 2009]. Exon marking and nucleosome occupancy between exons and introns also show only ~1.5-fold differences and nucleosome occupancy improved exon recognition only to a limited degree [Spies et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Histones around TSSs tend to be acetylated at H3K27 15, while those that demarcate transcriptional regulatory domains such as enhancers may be decorated by both H3K27acetylation and H3K4 monomethylation 16, 17, and these distal regulatory domains may be in anything from within kilobases to megabases away from the genes whose expression they regulate. H3K36 trimethylation is enrichment at transcribed exons 18 and histone acetylation at H3K9, 12 and 14 is also found around expressed genes 19. Expressed genes also display H4K20, H3K27 and H3K9 monomethylation 14 and H3K79 dimethylation 3.…”
Section: Chromatin Organizationmentioning
confidence: 98%